2013
DOI: 10.1186/1752-1947-7-31
|View full text |Cite
|
Sign up to set email alerts
|

The role of high mobility group box chromosomal protein 1 expression in the differential diagnosis of hepatic actinomycosis: a case report

Abstract: IntroductionPrimary hepatic actinomycosis is a rare disease, but is important in the differential diagnosis of hepatoma in endemic areas. As high mobility group box chromosomal protein 1 plays an important role in the pathogenesis of both acute and chronic inflammatory conditions, we postulate that high mobility group box chromosomal protein 1 may have a possible pathogenic role in hepatic actinomycosis. To the best of our knowledge, our report is the first to detect an association between highly elevated high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…PHA occurs worldwide, but only 87 cases were reported in English literature between 1966 and 2015; none of them were from mainland China. This case prompted us to review PHA cases reported from mainland China in Chinese literature, and share the experience with the colleagues in the rest of the world.…”
mentioning
confidence: 99%
“…PHA occurs worldwide, but only 87 cases were reported in English literature between 1966 and 2015; none of them were from mainland China. This case prompted us to review PHA cases reported from mainland China in Chinese literature, and share the experience with the colleagues in the rest of the world.…”
mentioning
confidence: 99%